Exploring and describing the growth points of learners as they encounter functions in equation form. - Clark, Robyn (My University, 2014)
This research report confirms the value of the Framework of Growth Points in a learner’s mathematical development in the area of functions in equation form. The study also shows that learners advance through the various growth points in a progressive, sequential fashion, which mirrors the results of Ronda’s study, on which a part of this study was based. The study was carried out in a high school in Johannesburg. Learners in Grades 9, 10 and 11 were required to do an assessment which tested for their achievement in different growth points. This study also explores the discourse of learners while they talked about the tasks in the assessment. A smaller sample of learners was interviewed so that the researcher could explore the nature of their discourse. This research report shows that there are patterns in the discourse of learners which can be related to the growth points that they achieve.
Keywords: Algebra--Study and teaching (Secondary)--South Africa.; Functional equations--Study and teaching (Secondary)--South Africa.; Mathematical ability--Testing.